Use of antibiotics by hospitalized elderly and changes in serum creatinine - Cristina Costa, Fabiane; Araújo Assis Viudes, Matheus; Moreira da Costa, Josiane (O Mundo da Saúde, 2020)
The rapid growth of the elderly population, associated with longer life expectancy, is associated with a higher prevalence of chronic non-communicable diseases, such as those of the cardiovascular, renal system and neoplasms. A large portion of these pathologies require hospitalization and their conditions require the use of antibiotics (ATB), whose indiscriminate use can lead to Acute Kidney Injury (AKI), which has serum creatinine as one of its markers. Therefore, the present study aimed to evaluate changes in serum creatinine of hospitalized elderly people submitted to antibiotic therapy in a university hospital. This was a cross-sectional study in which patients over 60 years old were identified during a period of 6 months and who used ATB, as well as had their serum creatinine measured. The variables age, gender, length of hospital stays and use of ATB were considered, as well as serum creatinine values before and after antibiotic therapy. A total of 796 patients participated in the study, 51.4% (409) of whom were male. Ages ranged from 60 to 109 years, with an average of 74.9 (± 9.6). It was identified that length of stay and use of ATB are variables that interfere with the increase in creatinine due to antibiotic therapy, which was observed in 75.5% of the patients. This leads to the reflection about a possible indiscriminate prescription of antimicrobials and their correlation to AKI.